'A Pure Dwelling Place for the Holy Spirit': John Wesley's Reception of the Homilies of Macarius. (January 2019) - Ford, Coleman M.
The focus of this essay is on how, and to what extent, John Wesley's doctrine of Christian perfection was influenced by his readings of the late fourth-century monastic preacher, Macarius Symeon. In this essay, I argue that Wesley focuses too narrowly upon Macarius's language of Christian perfection to the neglect of his broader theological reflection. In doing so, Wesley sets out to paint upon a doctrinal canvas using fourth-century paint, yet neglects some of the necessary hues and tones. Wesley's doctrine of Christian perfection evolved throughout his life, though his reliance upon Macarius is well noted in his writings. The difference, however, between the 18 th -century revival preacher and the fourth century Egyptian monk is a greater recognition of earthly struggle and sin in this present life. While Macarius uses perfection language, his notion of the Christian life provided a much more grounded reality of sin and fallen human nature, contrary to Wesley's rendering with his doctrinal formulation.